L12 phase reinforced FCC type multi-component alloy and preparation method thereof
By preparing L12 phase-strengthening FCC type multi-component alloy, using specific element combinations and thermomechanical treatment processes, the problem of insufficient strength of FCC type high-entropy alloy is solved, and the combination of high strength and good plasticity is achieved, which is suitable for a variety of structures Materials application.
Patent Information
- Application Number
- CN202411409835.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-10
AI Technical Summary
The existing FCC type high entropy alloy has low strength, which limits its wide application as a structural material.
By preparing an L12 phase-strengthening FCC-type multi-component alloy, using the combination of Ni, Co, Fe, Al, Ti and B elements, a structural structure of "fine crystal + annealed twin + L12 phase" was formed, combined with vacuum electromagnetic levitation Processes of smelting, solid solution treatment, liquid nitrogen rolling and recrystallization treatment.
The room temperature yield strength of the alloy is achieved to reach 1063MPa, the tensile strength reaches 1696MPa and the elongation of breaking reach 25.9%, which improves strength and plasticity and is suitable for the field of high-demand structural materials.
Smart Images

Figure CN119392080A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of high entropy alloys and preparation thereof, and in particular to an L12 phase strengthened FCC type multi-component alloy and a preparation method thereof. Background Art
[0002] In recent years, high entropy alloys have attracted widespread attention due to their unique structural characteristics and excellent properties, especially their excellent strength-ductility combination, excellent corrosion resistance and radiation resistance. Among them, face-centered cubic (FCC) high entropy alloys have attracted much attention due to their easy processing and excellent plasticity and toughness. Their potential application areas include engines, molds and tools, biomedical materials and electromagnetic materials. However, the strength of such materials is usually low, which limits their widespread application as structural materials. Therefore, how to obtain FCC-type high entropy alloys with both excellent strength and good plasticity has become a technical problem that needs to be solved urgently in this field. Summary of the invention
[0003] The purpose of the present invention is to provide an L12 phase strengthened FCC type multi-component alloy and a preparation method thereof to solve the problems existing in the above-mentioned prior art. The alloy of the present invention is a high entropy alloy with a "fine grain + annealing twin + L12 phase" structure, which has excellent strength and good plasticity.
[0004] To achieve the above object, the present invention provides the following solutions:
[0005] One of the technical solutions of the present invention is: an L12 phase strengthened FCC type multi-component alloy, which comprises the following components in atomic percentage: Ni 42-45%, Co 21-24%, Fe 7-10%, Al 9-12%, Ti 10-13% and B1-3%.
[0006] Furthermore, the L12 phase strengthened FCC type multi-component alloy has an L12 structural strengthening phase and an FCC matrix phase.
[0007] The present invention uses Ni, Co and Fe as alloys to form an FCC matrix. The formed NiCoFe matrix has good solid solubility for Al and Ti and can stably form an FCC matrix. Secondly, Ni and Co can form an L12 phase with good stability with Al and Ti, thereby enhancing the strength and thermal stability of the alloy. The introduction of Fe helps to improve the plasticity of the alloy and also inhibits the formation of brittle phases. Al and Ti are the main elements that form the L12 phase. When combined with Ni and Co, they can generate a Ni3 (Al, Ti) type L12 phase with good mechanical properties. In addition, the addition of Al and Ti can also improve the oxidation resistance and high temperature performance of the alloy.
[0008] The B element in the present invention improves the comprehensive properties of the alloy by inhibiting grain boundary embrittlement. Omitting or replacing the B element will lead to a significant decrease in the tensile strength, elongation and creep resistance of the alloy.
[0009] Technical solution 2 of the present invention: A method for preparing the above-mentioned L12 phase strengthened FCC type multi-component alloy comprises the following steps:
[0010] Take metal elements Ni, Co, Fe, Al, and Ti, clean them ultrasonically in alcohol, and weigh them according to atomic percentage, then mix the metal elements with B powder, smelt them several times, and then cast them to obtain alloy ingots;
[0011] The alloy ingot is subjected to solution treatment, deep cold rolling treatment and recrystallization treatment in sequence to obtain the L12 phase strengthened FCC type multi-component alloy.
[0012] Furthermore, the raw material is a high-purity metal with a purity of not less than 99.99wt.%.
[0013] The raw materials are of extremely high purity, which can avoid the introduction of other impurities and enable the alloy to exhibit better mechanical properties.
[0014] Furthermore, the smelting is vacuum electromagnetic suspension smelting, and the number of smelting is 8 to 10 times; the size of the mold used for pouring is 12mm×18mm×100mm.
[0015] Vacuum electromagnetic levitation melting can eliminate the contamination of the molten material by air molecules and the contamination of the molten material by the crucible material, thus obtaining the purest product.
[0016] Repeated smelting can obtain an alloy with uniform composition.
[0017] Selecting a mold size of 12mm×18mm×100mm can maximize the contact between the alloy melt and the circulating water-cooled copper mold, avoiding the phenomenon of inconsistent solidification rate caused by inconsistent conduction rate between the center and edge of the alloy ingot.
[0018] Furthermore, the cooling adopts circulating water cooling copper mold cooling.
[0019] Circulating water-cooled copper molds can increase the cooling rate of the melt during solidification and obtain finer grains.
[0020] Furthermore, the heating rate of the solution treatment is 5°C / min. After the sample is placed in the furnace, the temperature is raised to 1050°C and then kept at this temperature for 12 hours. The environment is flowing argon gas, and the cooling method is air cooling.
[0021] When the temperature of the solution treatment is 1050℃, the alloy composition can be homogenized and the element segregation can be reduced; the chemical properties of argon are inactive, and using it as a protective gas can isolate the air and prevent the oxidation of the sample. And the solution treatment time of 12h can make the composition of the cast alloy more homogenized.
[0022] Further, the low temperature rolling treatment is liquid nitrogen rolling treatment;
[0023] The liquid nitrogen rolling treatment method comprises: after each cold rolling treatment, soaking in liquid nitrogen for 15 minutes (the temperature is reduced to the same as the liquid nitrogen temperature, 77K); when the reduction amount is 25%, 50% and 75%, an intermediate annealing treatment is performed respectively until the total deformation amount reaches 90%.
[0024] Compared with traditional room temperature cold rolling, deep cryogenic treatment in liquid nitrogen environment has a stronger effect on grain refinement, while achieving similar plasticity and making the mechanical properties of the alloy better.
[0025] Furthermore, the heating rate of the intermediate annealing treatment is 5°C / min. The tube furnace is heated to 1050°C before the sample is placed therein and kept warm for 15 minutes. The environment is flowing argon gas and air cooling is used for cooling.
[0026] Intermediate annealing can effectively reduce the dislocation density in the alloy, reduce rolling stress and promote uniform deformation, improve the movement ability of dislocations in the alloy sample, and allow the alloy sample to continue to deform.
[0027] Furthermore, the heating rate of the recrystallization treatment is 5°C / min, and the sample is placed in the reaction mixture after the temperature reaches 1050°C, and the temperature is kept at this temperature for 30 to 90 minutes. The environment is flowing argon gas, and air cooling is used for cooling.
[0028] Controlling the temperature and time of the recrystallization treatment can cause the cold-rolled elongated grains to recrystallize, and can control the degree of crystallization, ensuring that the degree of crystallization reaches 80-95%, while retaining a certain density of dislocations.
[0029] The third technical solution of the present invention: an application of the above-mentioned L12 phase strengthened FCC type multi-component alloy in the fields of construction, bridges, automobile manufacturing or aerospace.
[0030] The present invention discloses the following technical effects:
[0031] (1) The L12 phase-reinforced FCC-type multi-component alloy of the present invention has an L12 phase and an FCC matrix phase (obtained based on the preparation method and elemental composition), has a certain density of geometrically required dislocations, and has excellent strength and ductility.
[0032] (2) The present invention uses high-purity pure metal as raw material and performs simple thermomechanical treatment to construct a "fine grain + annealing twin + L12 phase" structure to achieve the strengthening and toughening of the FCC type high entropy alloy, so that the room temperature yield strength of the alloy reaches 1063MPa, the room temperature tensile strength reaches 1696MPa, and the elongation at break reaches 25.9%. The strength of the alloy is improved and has excellent strength-plasticity matching. It can be applied to structural materials with high requirements, such as construction, bridges, automobiles, aerospace, etc., and has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 The microstructure diagram of the alloy ingot obtained by vacuum electromagnetic levitation melting in step (1) of Example 2 of the present invention. Among them, (a) is a macroscopic structure SEM image, (b) is a single grain SEM image, (c) is a SEM image of the L12 particle in the center of the grain, (d) is a TEM image of the L12 particle, (e) to (h) are high-resolution images and FFT images of the FCC phase and the L12 phase, and (i) is an inverse pole figure;
[0035] Figure 2 IPF diagrams, grain boundary and twin boundary distribution diagrams, and geometric required dislocation density diagrams of L12 phase strengthened FCC type multi-component alloys prepared by different recrystallization times in Examples 1 to 3 of the present invention, wherein (a) to (c) are IPF diagrams of the alloys prepared by Examples 1 to 3, (d) to (f) are grain boundary and twin boundary distribution diagrams of the alloys prepared by Examples 1 to 3, and (g) to (i) are geometric required dislocation density diagrams of the alloys prepared by Examples 1 to 3;
[0036] Figure 3 It is a curve chart of uniaxial tensile test results of the L12 phase strengthened FCC type multi-component alloy prepared in Examples 1 to 3 of the present invention and Comparative Example 1;
[0037] Figure 4 The mechanical properties of the L12 phase strengthened FCC type multi-component alloy prepared in Example 2 of the present invention are compared with the strength and plasticity of other high entropy alloys in a dual-phase structure, wherein (a) is a comparison chart of elongation and yield strength with other alloys, (b) is a comparison chart of elongation and tensile strength with other alloys, and (c) is a comparison chart of yield strength and tensile strength with other alloys. DETAILED DESCRIPTION
[0038] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0039] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0040] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0041] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0043] Example 1
[0044] A preparation method of L12 phase strengthened FCC type multi-component alloy:
[0045] (1) L12 phase strengthened FCC type multi-component alloy, the composition is as follows in terms of atomic percentage (at.%): 43.9% Ni, 22.4% Co, 8.8% Fe, 10.7% Al, 11.7% Ti, and 2.5% B.
[0046] Take metal single substances Ni, Co, Fe, Al, and Ti, clean them ultrasonically in alcohol, and then weigh (accurate to 0.001g) metal single substances according to atomic percentage (the raw materials are all high-purity metal particles with a purity of not less than 99.99wt.%, and a particle size of 3mm) and mix them with B powder, and then place them in a vacuum electromagnetic suspension melting furnace for vacuum electromagnetic suspension melting. During the melting process, first evacuate to negative pressure (10Pa), and then turn on the molecular pump to evacuate to 5×10 -3 Pa, high-purity argon is introduced to 75000pa, and the melting power is controlled to be 130kW. During the melting process, the molten pool is always in a suspended state under the action of electromagnetic force. After repeated melting for 8 times (each melting time is 5 min), it is poured into a water-cooled copper mold (size is 12 mm×18 mm×100 mm), and formed by circulating water cooling (10 min) to obtain an alloy ingot.
[0047] (2) The alloy ingot prepared in step (1) is placed in a vacuum tube furnace, heated to 1050°C at a heating rate of 5°C / min in a flowing argon environment, then kept at this temperature for 12 h (solution treatment for 12 h), and air-cooled to obtain a homogenized sample.
[0048] (3) The homogenized sample prepared in step (2) is subjected to liquid nitrogen rolling treatment (after 10 rolling passes, the reduction reaches 25%, after 11 rolling passes, the reduction reaches 50%, after 18 rolling passes, the reduction reaches 75%, and after 22 rolling passes, the reduction reaches 90%). After each cold rolling treatment, it is immersed in liquid nitrogen (the temperature is reduced to the same as the liquid nitrogen temperature, 77K). When the reduction is 25%, 50% and 75%, an intermediate annealing treatment is performed respectively (the tube furnace is heated to 1050°C at a heating rate of 5°C / min, and the sample with a reduction of 25%, 50% or 75% is placed in the tube furnace for 15 minutes, the environment is flowing argon gas, and the cooling method is air cooling) until the total deformation reaches 90%.
[0049] (4) After heating the tube furnace to 1050°C at a heating rate of 5°C / min under a flowing argon environment, the sample obtained in step (3) was placed in the tube furnace for 30 min (recrystallization treatment for 30 min), and air-cooled to obtain an L12 phase-strengthened FCC-type multi-component alloy (a face-centered cubic high entropy alloy with a "fine grain + annealing twin + L12 phase" structure).
[0050] The geometric required dislocation density of the alloy prepared in this example is 3.37×10 14 m -2, the average grain size is 7.97μm, and the volume fraction of annealed twins is 17.1%. This structure makes the alloy have both high yield strength and good ductility. After testing, the tensile strength of the alloy prepared in this embodiment is 1732MPa, the yield strength is 1104MPa, and the elongation at break is 20.8%.
[0051] Example 2
[0052] The same as Example 1, except that the recrystallization treatment time in step (4) is 45 minutes.
[0053] The alloy prepared in this example has a FCC+L12 dual-phase structure, and its geometric required dislocation density is 1.13×10 14 m -2 , the average grain size is 8.27μm, and the volume fraction of annealed twins is 26.6%. This structure makes the alloy have both high yield strength and good elongation. After testing, the tensile strength of the alloy prepared in this embodiment is 1696MPa, the yield strength is 1063MPa, and the elongation at break is 25.9%.
[0054] Example 3
[0055] The same as Example 1, except that the recrystallization treatment time in step (4) is 90 minutes.
[0056] The alloy prepared in this example has a FCC+L12 dual-phase structure, and its geometric required dislocation density is 0.34×10 14 m -2 , the average grain size is 8.96μm, and the volume fraction of annealed twins is 20.6%. This structure makes the alloy have high tensile strength and good elongation. After testing, the tensile strength of the alloy prepared in this embodiment is 1425MPa, the yield strength is 982MPa, and the elongation at break is 13.8%.
[0057] Comparative Example 1
[0058] Same as Example 2, except that B is not added.
[0059] The L12 phase strengthened FCC type multi-component alloy has the following composition, calculated by atomic percentage (at.%): 46.4% Ni, 22.4% Co, 8.8% Fe, 10.7% Al and 11.7% Ti.
[0060] According to tests, the alloy prepared in this embodiment has a tensile strength of 1274 MPa, a yield strength of 933 MPa, and an elongation at break of 5.3%.
[0061] Figure 1The microstructure diagram of the alloy ingot prepared by vacuum electromagnetic levitation melting in step (1) of Example 2 of the present invention. Among them, (a) is a macroscopic structure SEM image, (b) is a single grain SEM image, (c) is a SEM image of L12 particles in the center of the grain, (d) is a TEM image of L12 particles, (e) to (h) are high-resolution images and FFT images of FCC phase and L12 phase, and (i) is an inverse pole figure.
[0062] from Figure 1 It can be seen from the graph that there are nano-scale ellipsoidal precipitates in the grains of the alloy ingot. TEM observation shows that the alloy is an FCC matrix and the ellipsoidal precipitates are L12 phases. From the corresponding EBSD graph, it can be seen that the average grain size of the alloy ingot is 69.71μm.
[0063] Figure 2 The IPF diagrams, grain boundary and twin boundary distribution diagrams and geometric required dislocation density diagrams of the L12 phase strengthened FCC type multi-component alloys prepared by Examples 1 to 3 of the present invention using different recrystallization times, wherein (a) to (c) are the IPF diagrams of the alloys prepared by Examples 1 to 3, respectively, (d) to (f) are the grain boundary and twin boundary distribution diagrams of the alloys prepared by Examples 1 to 3, respectively, and (g) to (i) are the geometric required dislocation density diagrams of the alloys prepared by Examples 1 to 3, respectively.
[0064] from Figure 2 It can be seen that with the increase of annealing time (recrystallization treatment time) after rolling (30-90min), the grains gradually grow larger, and the volume fraction of twin boundaries first increases and then decreases, reaching a peak of 26.6% at 45min. At the same time, with the extension of annealing time, the density of geometrically required dislocations gradually decreases, and the sample is almost completely recrystallized at 90min.
[0065] Figure 3 It is a curve chart of uniaxial tensile test results of the L12 phase strengthened FCC type multi-component alloy prepared in Examples 1 to 3 of the present invention and Comparative Example 1.
[0066] Figure 3 Re-30 is the alloy prepared in Example 1, Re-45 is the alloy prepared in Example 2, Re-90 is the alloy prepared in Example 3, Homogenized is the homogenized alloy obtained by solution treatment in step (2) of Example 1, and Re-45 (B-free) is the alloy prepared in Comparative Example 1 without adding B element.
[0067] from Figure 3It can be seen that the strength and plasticity of the alloy prepared by the present invention increase first and then decrease with the recrystallization time. The mechanical properties are best in Example 2, and its yield strength and tensile strength are respectively increased by 14.9% and 63.07% compared with the homogenized alloy, and the elongation at break is greatly improved. The mechanical properties of the alloys prepared in Examples 1 to 3 are much higher than those of the homogenized samples. In addition, by comparing the mechanical properties of Example 2 and Comparative Example 1 with or without the addition of B, it can be found that the B element significantly improves the elongation at break of the alloy.
[0068] Figure 4 The mechanical properties of the L12 phase strengthened FCC type multi-component alloy prepared in Example 2 of the present invention are compared with the strength and plasticity of other dual-phase structured high entropy alloys (other L12 phase strengthened FCC structured high entropy alloys), wherein (a) is a comparison chart of elongation and yield strength with other alloys, (b) is a comparison chart of elongation and tensile strength with other alloys, and (c) is a comparison chart of yield strength and tensile strength with other alloys.
[0069] from Figure 4 It can be seen that the mechanical properties of the L12 phase strengthened FCC type multi-component alloy prepared in Example 2 of the present invention are better than the mechanical properties of other L12 phase strengthened FCC medium-high entropy alloys.
[0070] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. An L12 phase strengthened FCC type multi-component alloy, characterized in that: Calculated in atomic percentage, it includes the following components: Ni 42-45%, Co 21-24%, Fe 7-10%, Al 9-12%, Ti 10-13% and B 1-3%.
2. The L12 phase strengthened FCC type multi-component alloy according to claim 1, characterized in that: The L12 phase strengthened FCC type multi-component alloy has an L12 structural strengthening phase and an FCC matrix phase.
3. A method for preparing the L12 phase strengthened FCC type multi-component alloy according to any one of claims 1 to 2, characterized in that: The following steps are involved: Take metal elements Ni, Co, Fe, Al, and Ti, clean them ultrasonically in alcohol, and weigh them according to atomic percentage, then mix the metal elements with B powder, smelt them several times, and then cast them to obtain alloy ingots; The alloy ingot is subjected to solution treatment, deep cold rolling treatment and recrystallization treatment in sequence to obtain the L12 phase strengthened FCC type multi-component alloy.
4. The preparation method according to claim 3, characterized in that: The smelting is vacuum electromagnetic suspension smelting, and the number of smelting is 8 to 10 times.
5. The preparation method according to claim 3, characterized in that: The heating rate of the solution treatment is 5°C / min, and the temperature is heated to 1050°C and then kept for 12 hours. The environment is flowing argon gas, and the cooling method is air cooling.
6. The preparation method according to claim 3, characterized in that: The deep cold rolling treatment is liquid nitrogen rolling treatment; The liquid nitrogen rolling treatment method comprises: soaking in liquid nitrogen to 77K after each rolling treatment; performing intermediate annealing treatment respectively when the reduction amount is 25%, 50% and 75%, until the total deformation amount reaches 90%.
7. The preparation method according to claim 6, characterized in that: The heating rate of the intermediate annealing treatment is 5°C / min. After the temperature reaches 1050°C, the sample is placed in the sample and kept warm for 15 minutes. The environment is flowing argon gas and the cooling method is air cooling.
8. The preparation method according to claim 3, characterized in that: The heating rate of the recrystallization treatment is 5°C / min. After the temperature is raised to 1050°C, the sample is placed in the sample and kept warm for 30 to 90 minutes. The environment is flowing argon gas and the cooling method is air cooling.
9. Application of the L12 phase strengthened FCC type multi-component alloy according to claim 1 in the fields of construction, bridges, automobile manufacturing or aerospace.
Citation Information
Patent Citations
Ni-Co-Fe-B series eutectic high-entropy alloy and preparation method and application thereof
CN113444954A